Daily Living Activities of School Age Children with Acute Lymphocytic Leukemia at Welfare Pediatric Teaching Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): The study aims to assess daily living activities domain of school age children with acutelymphocytic.Methods: A descriptive study, conducted in Baghdad City from 13 of February to 20 of May 2016. Apurposive sample of 50 children with acute lymphocytic leukemia at welfare pediatric teaching hospital andchild central pediatric hospital. The study instrument was consists of three parts, the first was demographicdata demographic characteristics of the child, the second part is related to the symptoms and clinical signsand complications phenomenon on the child, and the third part related to the daily activities for school agechildren.. Data was analyzed using (SPSS) version 25. The data analysis for this study included descriptiveand inferential statistical analysis.Results: The results of our study showed that (50%) within age groups (6-7)years , (60%) were males,(66%) of them were continuing school attendance, (56%) within class level (1-2) , the highest percentage(58%) of the study sample are not miss school. there is significant association between participants DLAand their demographic characteristics such as age, gender, school situation and education level, at p-valueof (0.007, 0.004, 0.013,and 0.001) respectively, (96%) of them complain from yellowing and pale skin,(70%) complain from anemia, vast majority of them have moderate daily activities. that there is significantassociation between participants’ DAL and their Symptoms and Clinical Signs and Complications of theChild with Acute Lymphocytic Leukemia of, breathing difficulties , Yellowing and pale skin, bleeding andbruising and Anemia, at p-value of (0.003, 0.002, 0.001,and 0.005) respectively
Keywords: Children, Acute Lymphocytic Leukemia, Welfare Pediatric Teaching Hospital